Chiral Spirocyclic Phosphoric Acid‐Catalyzed Synthesis of 4‐Alkyl‐3, 4‐dihydropyrimidin‐2(1H)‐one Derivatives by Asymmetric Biginelli Reactions. Issue 4 (20th February 2020) - Guo, Yongbiao; Gao, Zhenhua; Wang, Kang; Li, Junchen; Bi, Xiaojing; Guo, Lei; Liu, Haibo; Shi, Enxue; Xiao, Junhua
Abstract: A chiral spirocyclic phosphoric acid‐catalyzed asymmetric Biginelli reaction based on aliphatic aldehydes has been realized for the synthesis of biologically important and synthetically useful 4‐alkyl‐3, 4‐dihydropyrimidin‐2‐(1H)‐one (4‐alkyl−DHPM) skeletons in good yield and with high levels of enantioinduction. The utility of this transformation was further demonstrated by direct thionation and C−C/C−N bond construction to provide a series of 4‐alkyl−DHPMs derivatives without any loss of optical activity, providing streamlined access to the formal synthesis of Batzelladine A. Abstract : A chiral spirocyclic phosphoric acid‐catalyzed asymmetric Biginelli reaction based on aliphatic aldehydes has been realized for the synthesis of biologically important and synthetically useful 4‐alkyl‐3, 4‐dihydropyrimidin‐2‐(1H)‐one (4‐alkyl−DHPM) skeletons in good yield and with high levels of enantioinduction.